2015
DOI: 10.1007/s11340-015-9994-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Crashworthiness of Functionally Graded Thickness Thin-Walled Tubular Structures

Abstract: This paper is an experimental investigation of the crashworthiness behavior of functionally graded thickness (FGT) thin-walled tubular structures. Aluminum alloy AA6061-T5 was chosen because of its high strength to weight ratio and high stiffness. A series of FGT tubes with thicknesses varying linearly from one end to the other were evaluated in quasi-static crushing and three-and four-point bending tests for the purpose of evaluating their energy absorption characteristics. AA6061-T5 FGT tubes with four thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Based on the theoretical analysis in Section 3, two parameters are essential for predicting the mean load of the DSG tube theoretically: the global average thickness of the tube , which can be easily obtained based on the geometric configuration, and average thickness of the EEAR , which can be determined for a known half wavelength H using (25). However, calculating H using (16) and (19) requires a known value of , meaning the calculation process is circular.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the theoretical analysis in Section 3, two parameters are essential for predicting the mean load of the DSG tube theoretically: the global average thickness of the tube , which can be easily obtained based on the geometric configuration, and average thickness of the EEAR , which can be determined for a known half wavelength H using (25). However, calculating H using (16) and (19) requires a known value of , meaning the calculation process is circular.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Baykasoglu and Cetin studied crashworthiness of circular tubes with gradient thicknesses [18]. The crushing resistances of circular tubes with axially graded thickness were then explored by Xu et al [19]. Graded thicknesses in the longitudinal direction were also extended to square [20] and multicell columns [21]; and corresponding performance optimization was presented.…”
Section: Introductionmentioning
confidence: 99%
“…34 The crashing performance of circular tubes with linearly distributed thicknesses in the longitudinal direction was experimentally studied by Xu et al. 35 Ying et al. 36 introduced the graded strength defined by a power-law function with a gradient exponent.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of advanced configurations with gradient properties, there are a large number of published literatures, which have shown that those structures could collapse in a more controlled manner and have a remarkable energy-absorbing efficiency. [31][32][33] For example, the effects of graded or variable thickness on energy absorption characteristics of aluminium circular tubes under axial crushing were numerically investigated by Baykasoglu et al 34 The crashing performance of circular tubes with linearly distributed thicknesses in the longitudinal direction was experimentally studied by Xu et al 35 Ying et al 36 introduced the graded strength defined by a power-law function with a gradient exponent. And an optimization design was further performed to achieve the matching between mechanical properties and safety performance of tubular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Zhang 8 carried out experimental and numerical studies on the impact characteristics of tapered tubes with variable thickness under axial load. Xu et al 9 carried out experimental studies on the crashworthiness of thinwalled structures with FGT. Xu 10 found that FGT tubes had the advantage of reducing the initial peak force and improving EA compared to circular and conical tubes of uniform thickness.…”
Section: Introductionmentioning
confidence: 99%